Optimization and reliability of an electrical network - Nedeva, Cvetana (Ann. Sofia Univ. Fac. Math. and Inf., 1996)
An electric power system and tests for its reliability are considered. In order to get a reliable network, we have to change some of the branches. The problem for the optimal exchange is formulated as a two-stage stochastic programming problem, solvable by stochastic quasigradient methods.